Towards understanding structural changes of photoperiod-sensitive sorghum biomass during sulfuric acid pretreatment - Xu, Feng; Shi, Yong-Cheng; Wang, Donghai (My University, 2013)
Wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS) were employed to investigate the structural changes of photoperiod-sensitive sorghum biomass in both crystalline and amorphous domains after sulfuric acid pretreatment. WAXD results suggested that the crystalline cellulose melted at 120 °C without significant polymer degradation and cellulose went through a simultaneous hydrolysis and crystallization at 160 °C. Both the cellulose crystallinity and the crystal size increased as the temperature increased, which might lower cellulose digestibility. The efficiency of enzymatic hydrolysis (EEH) increased because the cellulose protective structure was compromised and most hemicellulose was removed, resulting in an increase in total surface area as suggested by SAXS results. The radius of gyration of the polymer structure decreased and the lamellar structure was destroyed after pretreatment. Both the EEH and cellulose degradation increased as the temperature increased. The total glucose yield increased to 79.7% as the temperature increased to 160 °C.
Keywords: Biomass structure; WAXD; SAXS; Cellulose; Acid pretreatment; Enzymatic hydrolysis; Sorghum